Challenges in open innovation practices for industries - Parida, Vinit (Luleå tekniska universitet, Innovation och Design, 2009)
The development of open innovation model is gaining interest from practitioners and researchers. This paradigm shift suggests that firms can and should use external and internal ideas, and internal and external paths to market their innovative products. The result of this approach leads to higher growth potential and effective innovation process. However, the adoption of open innovation practices requires considerable change in the overall business model and processes. This naturally creates several challenges (internal and external issues) that can hinder the transformation. Thus, this study makes an attempt to identify and explore the challenges associated with open innovation practices, and also suggests possible way in which they can be converted into potential opportunities. The results suggest that although challenges exist there are several ways in which most of them can be resolved. Godkänd; 2009; 20081207 (vinpar) Fastelaboratoriet - VINNEXC